The Influence of the Quality of Human Resource Management on Public Service Performance at the Karangpawitan Subdistrict Office, Karawang Regency - Haryani, Siti; Kristanto, Yudi; Army, Widya Lelisa (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research is motivated by the low level of education of employees at the Karangpawitan Subdistrict Office, Karawang Regency, which has an impact on the activities of carrying out tasks in their services. The phenomenon that occurs is that in an effort to carry out public services, officials often make mistakes that should not occur, for example in complying with working hours regulations, many employees arrive late and do not come to work. This makes the performance of an organization hampered in completing work that should be done. has been determined by time. Basically, an entry schedule is very necessary to improve the employee's performance. The aim of this research is to find out whether the quality of HR management influences the quality of public services. The research methodology uses quantitative methods with associative techniques. The findings in the field show that there is an influence between the quality of HR management on public service performance of 34%, the remaining 66% is determined by other factors outside the Quality of HR Management. The originality of this research is that it was originally carried out by the researcher without plagiarizing from other research with the same theme.